Enhancement of Energy Transfer Efficiency with Structural Control of Multichromophore Light‐Harvesting Assembly. Issue 20 (19th August 2020) - Oh, Inhwan; Lee, Hosoowi; Kim, Tae Wu; Kim, Chang Woo; Jun, Sunhong; Kim, Changwon; Choi, Eun Hyuk; Rhee, Young Min; Kim, Jeongho; Jang, Woo‐Dong; Ihee, Hyotcherl
Abstract: Multichromophore systems (MCSs) are envisioned as building blocks of molecular optoelectronic devices. While it is important to understand the characteristics of energy transfer in MCSs, the effect of multiple donors on energy transfer has not been understood completely, mainly due to the lack of a platform to investigate such an effect systematically. Here, a systematic study on how the number of donors ( n D ) and interchromophore distances affect the efficiency of energy transfer ( η FRET ) is presented. Specifically, η FRET is calculated for a series of model MCSs using simulations, a series of multiporphyrin dendrimers with systematic variation of n D and interdonor distances is synthesized, and η FRET s of those dendrimers using transient absorption spectroscopy are measured. The simulations predict η FRET in the multiporphyrin dendrimers well. In particular, it is found that η FRET is enhanced by donor‐to‐donor energy transfer only when structural heterogeneity exists in an MCS, and the relationships between the η FRET enhancement and the structural parameters of the MCS are revealed. Abstract : A principle for accurately predicting the efficiency of Förster resonance energy transfer ( η FRET ) in multichromophore systems (MCSs) is presented. Simulations on model MCSs and spectroscopic experiments on multiporphyrin dendrimers show how the number of donors and interchromophore distances affect η FRET and reveal that structural heterogeneity plays a key role in enhancing η FRET in MCSs.